Tunneling Nanotubes Facilitate Intercellular Protein Transfer and Cell Networks Function - Turos-Korgul, Laura; Kolba, Marta Dorota; Chroscicki, Piotr; Zieminska, Aleksandra; Piwocka, Katarzyna (Frontiers in Cell and Developmental Biology, 2022)
The past decade witnessed a huge interest in the communication machinery called tunneling nanotubes (TNTs) which is a novel, contact-dependent type of intercellular protein transfer (IPT). As the IPT phenomenon plays a particular role in the cross-talk between cells, including cancer cells as well as in the immune and nervous systems, it therefore participates in remodeling of the cellular networks. The following review focuses on the placing the role of tunneling nanotube-mediated protein transfer between distant cells. Firstly, we describe different screening methods used to study IPT including tunneling nanotubes. Further, we present various examples of TNT-mediated protein transfer in the immune system, cancer microenvironment and in the nervous system, with particular attention to the methods used to verify the transfer of individual proteins.